Grounds for refusal to initiate civil case: changes are needed - Skobelev, Vladimir P. (Journal of the Belarusian State University. Law, 2019)
The paper analyzes in detail a number of grounds for refusal to initiate civil proceedings, in particular, related to cases applying to the court attorney, not authorized representatives, incapable persons and others. The author proposes to limit the prosecutor’s right to appeal in court to protect the interests of others, to free procedural plaintiffs from having to comply with the order of pre-trial settlement of cases, to clarify some of the existing and introduce new grounds for refusal to initiate a case (termination of the proceedings). The article contains a number of other proposals for improvement of the civil procedural law and practice of its implementation. Proposals for improving the legislation accompanied by specific editions of the new (modified) rules.
Keywords: civil proceedings; institution of a civil proceedings; ground to refuse to initiate a civil case